(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study employs a qualitative descriptive research method aimed at exploring and analyzing the implementation of transformational leadership by school principals in improving the quality of learning at State Vocational High Schools (SMK Negeri) in Palangka Raya City, Central Kalimantan Province. The qualitative approach was chosen to provide an in-depth understanding of leadership practices, attitudes, and their impact on teaching and learning processes. Data collection techniques included in-depth interviews, direct observations, and documentation studies. Participants in the study consisted of school principals, teachers, and administrative staff selected through purposive sampling, based on their roles and relevance to the research objectives. Data analysis was conducted using interactive model analysis consisting of data reduction, data display, and conclusion drawing/verification, as developed by Miles and Huberman. The validity of the data was ensured through triangulation of sources and methods, prolonged engagement, and member checking to ensure credibility, dependability, and confirmability of findings. This methodological approach enabled the researchers to interpret the transformational leadership behaviors practiced by the principals, identify their strategic efforts to improve learning quality, and understand the contextual challenges they face within the school environment.